Current status of hepatocyte xenotransplantation. (November 2015) - Meier, Raphael P.H.; Navarro-Alvarez, Nalu; Morel, Philippe; Schuurman, Henk-Jan; Strom, Stephen; Bühler, Leo H.
Abstract: The treatment of acute liver failure, a condition with high mortality, comprises optimal clinical care, and in severe cases liver transplantation. However, there are limitations in availability of organ donors. Hepatocyte transplantation is a promising alternative that could fill the medical need, in particular as the bridge to liver transplantation. Encapsulated porcine hepatocytes represent an unlimited source that could function as a bioreactor requiring minimal immunosuppression. Besides patients with acute liver failure, patients with alcoholic hepatitis who are unresponsive to a short course of corticosteroids are a target for hepatocyte transplantation. In this review we present an overview of the innate immune barriers in hepatocyte xenotransplantation, including the role of complement and natural antibodies; the role of phagocytic cells and ligands like CD47 in the regulation of phagocytic cells; and the role of Natural Killer cells. We present also some illustrations of physiological species incompatibilities in hepatocyte xenotransplantation, such as incompatibilities in the coagulation system. An overview of the methodology for cell microencapsulation is presented, followed by proof-of-concept studies in rodent and nonhuman primate models of fulminant liver failure: these studies document the efficacy of microencapsulated porcine hepatocytes which warrants progress towards clinical application. Lastly, we present an outline of a provisional clinical trial, that upon completion of preclinical work could start within the upcoming 2–3 years. Highlights: An overview is presented of the innate immune barriers in hepatocyte xenotransplantation. Some illustrations are presented of physiological species incompatibilities in hepatocyte xenotransplantation. An overview of methodology in cell microencapsulation is presented. An overview of proof-of-concept studies using microencapsulated porcine hepatocyte xenotransplantation are presented. An outline of a provisional clinical trial is presented.